Radiobiological comparison of hypofractionated accelerated partial-breast irradiation (APBI) and single-dose intraoperative radiotherapy (IORT) with 50-kV X-rays - Herskind, Carsten; Wenz, Frederik (Strahlentherapie und Onkologie, 2010)
Intraoperative radiotherapy (IORT) of the tumor bed in early breast cancer is presently performed with a single dose of 50-kV X-rays from a miniaturized X-ray machine using spherical applicators. The purpose was to model the biological effect of hypofractionated accelerated partial-breast irradiation (APBI) with ten fractions.
Englische Zusammenfassung: Strahlenbiologischer Vergleich hypofraktionierter, akzelerierter Teilbrustbestrahlung (APBI) und einzeitiger intraoperativer Radiotherapie (IORT) mit 50-kV-Rontgenstrahlen
Gesehen am 03.05.2023